Perbedaan Daya Tahan Aerobik Mahasiswa Fakultas Ilmu Keolahragaan Universitas Cendrawasih Setelah Melakukan Tari Yospan - Yohanis Manfred Mandosir; Junalia Muhammad; Sopater Asyena Pais; Budi Kristanto; Nasruddin (Indonesian Journal of Kinanthropology (IJOK), 2022)
Background: Yospan dance is a form of participation to protect Papuan cultural values and can be used to improve student fitness. The purpose of this study was to determine whether the Yospan dance had an effect on the aerobic endurance of FIK-2019 students Methods: This study is a quasi-experimental study with one group pretest and posttest design, with variables: 1. Yospan dance performed to the accompaniment of wasimba song and 2. Aerobic endurance measured by running 2.4 km. The population in this study were all FIK Uncen students and the sample was FIK students class 2019 who contracted the Yospan course totaling 14 respondents. Results: The results of the study were analyzed using paired t-tests and the result was that there was no effect of Yospan dance on the aerobic endurance of FIK 2019 students, as evidenced by the value of Sig = 0.20 > 0.05 Conclusions: Based on the results of the Paired T test and the discussion above, the conclusion that can be drawn from this study is that there is no difference in the aerobic endurance of FIK Uncen students before and after the Yospan dance practice.